Effect of a noncircular shape of the torus on the magnetic surfaces of l=1 torsatron - Kotenko, V. G. (Вопросы атомной науки и техники, 2015)
The paper presents the numerical calculation results on the magnetic field produced by one helical winding laying on the surface of a noncircular torus. The influence of the chosen poloidal cross-section shape of the torus on the parameters of the closed magnetic surface configuration has been investigated. The calculation results show that the change of a torus with circular cross-section by a torus with noncircular cross-section in the l=1 torsatron under consideration decreases the value of the mirror ratio on the magnetic surfaces by a factor of ~8. And other parameters of magnetic surfaces were changed no more than by a factor of 1.5 to 2. A feasibility of the simplest torsatron with central stochastic magnetic field line region is discussed. Виконані чисельні розрахунки магнітного поля, що створюється однією гвинтовою обмоткою, що лежить на поверхні некругового тора. Вивчено вплив обраної форми полоїдального перерізу тора на параметри конфігурації магнітних поверхонь. Розрахунками виявлено, що в розглянутому варіанті l=1 торсатрона перехід від кругової до некругової форми тора призводить до зменшення величини коркового відношення на магнітних поверхнях у ~ 8 разів. При цьому інші параметри магнітних поверхонь змінюються не більше, ніж в 1,5…2 рази. Дискутується можливість створення l=1 торсатрона з центральною стохастичною областю силових ліній магнітного поля. Проведены численные расчеты магнитного поля, создаваемого одной винтовой обмоткой, лежащей на поверхности некругового тора. Изучено влияние выбранной формы полоидального сечения тора на параметры конфигурации замкнутых магнитных поверхностей. Расчетами показано, что в рассмотренном варианте l=1 торсатрона переход от круговой к некруговой форме тора приводит к уменьшению величины пробочного отношения на магнитных поверхностях в ~8 раз. При этом другие параметры магнитных поверхностей изменяются не более, чем в 1,5…2 раза. Обсуждается возможность реализации l=1 торсатрона с центральной стохастической областью силовых линий магнитного поля.